Conflitos contemporâneos decorrentes da presença da religião no espaço público: uma reflexão a partir da abordagem de Luiz Antônio Cunha e do observatório da laicidade - Ferreira, Valéria Fernanda Silveira (2024)
Within this production, drawing from the main works of Luiz Antônio Cunha, a professor and researcher in the field of Brazilian Education History, particularly concerning the state and educational secularism, and leveraging the available texts from the Observatory of Secularism in Education, our objective is to elucidate the trajectory of the mentioned author, and also seek to disseminate his conception of the term secularism and its relationship with education. The methodology employed for the completion of this work involved bibliographic research using works authored by Luiz Antônio Cunha, Roseli Fischamnn, Carlos Roberto Jamil Cury, José Luis Derisso, and others, and documentary research focusing on the Federal Constitution, Guidelines and Bases of the National Education Law, and the National Common Curricular Base. The text unfolds in three chapters: the first one is addressed to the system of union, Monarchy, and Republic, in addition to discussing the religious influence in Brazil. In the second chapter, our discussion engages with the contemporary debate on Religious Education based on authors who advocate the “Secular Religious Education”. In the third chapter, we address the regression post the 2018 elections, weaving observations on topics such as gender ideology, the School Without Party, homeschooling, and the influence of the motto "God, homeland, and family." This analysis unveils the challenges faced during the Bolsonaro government and the setback of secularity during his four-year term.